Analisis Perencanaan Infrastruktur Teknologi Informasi dalam Mendukung Transformasi Digital - Jodi Putra Aljabbar; M.Zacky Aulya; Mahendra Gilang; Ilham Swandanang; Dicky Pratama (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
Digital transformation has become a strategic necessity for both public and private organizations in improving efficiency, service quality, and competitiveness in the digital era. The success of digital transformation is greatly influenced by the readiness and planning of integrated and sustainable IT infrastructure. This study aims to analyze the role of IT infrastructure planning in supporting the implementation of organizational digital transformation. The method used is a systematic literature review of scientific publications relevant to the topic of IT infrastructure, strategic information system planning, and digital transformation. The review results indicate that IT infrastructure serves as the main foundation of digital transformation, encompassing hardware, software, networks, data centers, information security, and human resources. Poorly planned IT infrastructure has the potential to cause various issues, such as limited technology capacity, digital divides, cybersecurity risks, and investment inefficiencies. Therefore, strategic IT infrastructure planning that aligns with the organization's vision is required, supported by adequate funding, human resource competency development, and adaptive digital leadership to ensure the successful and sustainable implementation of digital transformation.